'You are not born being racist, are you?' Discussing racism with primary aged-children. Issue 4 (3rd July 2016) - Priest, Naomi; Walton, Jessica; White, Fiona; Kowal, Emma; Fox, Brandi; Paradies, Yin
Abstract : Ethnic-racial socialisation is broadly described as processes by which both minority and majority children and young people learn about and negotiate racial, ethnic and cultural diversity. This article extends the existing ethnic-racial socialisation literature in three significant ways: (1) it explores ways children make sense of their experiences of racial and ethnic diversity and racism; (2) it considers ways children identify racism and make distinctions between racism and racialisation; and (3) it examines teacher and parent ethnic-racial socialisation messages about race, ethnicity and racism with children. This research is based on classroom observations, semi-structured interviews and focus groups with teachers, parents and students aged 8–12 years attending four Australian metropolitan primary schools. The findings reveal that both teachers and parents tended to discuss racism reactively rather than proactively. The extent to which racism was discussed in classroom settings depended on: teachers' personal and professional capability; awareness of racism and its perceived relevance based on student and community experiences; and whether they felt supported in the broader school and community context. For parents, key drivers for talking about racism were their children's experiences and racial issues reported in the media. For both parents and teachers, a key issue in these discussions was determining whether something constituted either racism or racialisation. Strategies on how ethnic-racial socialisation within the school system can be improved are discussed.